Identification of Mollusca Types Around Bungus Beach Padang - Intan Permata Alfi; Gusmaweti Gusmaweti (RADINKA JAYA UTAMA PUBLISHER, 2023)
Mollusca animals have a soft body, not segmented, most of the shell is made of calcium carbonate. Taxonomic identification is carried out to find out the types of Mollusca animals as well as for collections. This research aims to determine the types of Mollusca animals around Bungus Beach Padang. This type of research is descriptive with roaming method. The cruising method is carried out by tracing the beach as far as the tides are ± 1 km long and 8 meters wide. Molluscs were taken directly for three times, and tested the water with physical and chemical factor parameters. The results obtained from the identification of Mollusca species found in the form of shells consisting of two classes, namely the Bivalvia class and the Gastropod class. The total number of individuals is 202 individuals. The most commonly found molluscs are the class Bivalvia with 17 species. The most abundant species and always found in each repetition was Soletellina diphos with 29 individuals, at least Meretrix lyrata, Barbatia fusca with 1 individual. Class Gastropods found as many as 14 species. The species most commonly found was Cypraea vitellus with 15 individuals, the least found were Cypraea leviathan, Murex trapa, Bufonaria rana, Turbo setosus, Pomacea sp., Phenacolepas sp. amounted to 1 individual. Identification of the types of Mollusca animals can be identified based on the morphology of their shells and can also match the Mollusca images that have been obtained with the identification book. From the results of this study it can be concluded that the identification of the types of Mollusca animals can be known based on the morphology of their shells and can also match the Mollusca images that have been obtained with identification books. The results of the research are recommended for further researchers to find the types of Mollusca animals as a whole, especially on the beach.